Precision Medicine Applied Concepts of Pharmacogenomics in Patients with Various Diseases and Polypharmacy - Turgeon, Jacques; Michaud, Veronique (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This colligated Special Issue of Pharmaceutics on Precision Medicine: Applied Concepts of Pharmacogenomics in Patients with Various Diseases and Polypharmacy offers to the reader a series of articles that describe the concept of Precision Medicine, discuss its implementation process and limitations, demonstrate its value by illustrating some clinical cases, and open the door to new and more sophisticated techniques and applications.